108k views
4 votes
Y= -1.7043x^2 +124.38x -358.51

User Solidcell
by
5.3k points

1 Answer

3 votes

Answer:

X - Y = 3.0062,

X -Y = 69.973

Explanation:

Given equation is

-1.7043x² + 124.38x - 358.51 = y

This equation can be written as

x² - 72.98x + 210.35

Or, x² - 69.973x - 3.0062x + 210.35

Or, x(x - 69.973) - 3.0062(x - 69.973)

So, (x - 69.973) (x - 3.0062)

Now this two factors are equal to y

x - 69.973 = y and x - 3.0062 = y

Hence X - Y = 69.973 and X - Y = 3.0062 Answer

User Jim Munro
by
5.0k points